(3aJM GdQMef aj aVGFd QeVGfs - (3GdbGhbLj GdWQGHdSj GdMfaj, CHh GdeMGSf, , eMeO Hf Ndjd Hf EHQGgje, J(B1305(3g`s ((3eMeO Hf MSjf GdeNddGJj GdTGaYj GdejOGfjs)
(3ChdgG (B:s
(3hHg fSJYjf GdMeO ddg QH GdYGdejf hHYO agPG TQM Ydi eNJUQ jGbhJ GdSMjej jMd CdaGXg hjHjf eQGOg hSejJg aJM GdQMef aj aVGFd QeVGfs
(3BNQgG (B:s
(3abGd(B: (3dYdg bUO hbJG UGajG HcOQI aCNHQg HGdbUI aJYLH hbGd eKd QGHYI jaYd gPG aj MbgG gj hGddg SjOI ReGffGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 118s
(3eYLe GdeDdajf(B: 3 / 278s
(3EjVGM Gdecfhf(B: 2 / 164s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs